IMPLEMENTASI TEKNIK STORYTELLING UNTUK MENINGKATKAN MINAT BACA DAN KETERAMPILAN BERBICARA SISWA KELAS I SD NEGERI 1 BARENGLOR - Rahmawati, Esti; Dwi Bambang Putut Setiyadi; Triyono, Triyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Basic literacy skills, particularly reading and speaking, play an important role in supporting students’ academic and social development in elementary school. Low reading interest and limited speaking skills are still commonly found among early grade students. This study aimed to describe the implementation of storytelling techniques in improving reading interest and speaking skills of first-grade students at SD Negeri 1 Barenglor. The research employed a qualitative approach using Classroom Action Research (CAR) based on the Kemmis and McTaggart model which consisted of planning, action, observation, and reflection conducted in two cycles. The subjects of this study were 28 first-grade students. Data were collected through observation, questionnaires, speaking tests, and documentation. Data analysis was conducted using descriptive qualitative and simple quantitative analysis through mean scores and percentages. The results showed that the implementation of storytelling techniques improved students’ reading interest and speaking skills. The average score of reading interest increased from 46.55 in the pre-action stage to 54.40 in Cycle I and 72.44 in Cycle II. The percentage of students with high reading interest also increased to 78.57%. Speaking skills improved as indicated by the increase in the average score from 47.27 in the pre-action stage to 57.76 in Cycle I and 75.84 in Cycle II, with 75% of students reaching the high category. These findings indicate that storytelling techniques are effective in improving reading interest and speaking skills of early grade elementary school students.